The Roles of Islamic Organizations in Civil Society and Political Society: Malaysia and Indonesia Compared - Aisah Putri (Journal of Indonesian Social Sciences and Humanities, 2016)
In both Malaysia and Indonesia, Islamic organizations have played signifcant roles not only in civil society, but also in political society. By contrasting the Malaysian and Indonesian cases, this paper builds a notion arguing that it is possible for the Islamic organizations in civil society to objectively and actively oversee the state even when they are strongly linked to political parties. However, it needs specific conditions, namely a democratic system, a weak political coalition, and an independent integration process to allow Islamic organizations to move into political society. This argument is also antithetical to a popular neo-Tocquevilleans argument that civil society should be separated from political society to function effectively.